3D Printing for Complex Cranial Surgery Education: Technical Overview and Preliminary Validation Study - Graffeo, Christopher S; Perry, Avital; Carlstrom, Lucas P; Peris-Celda, Maria; Alexander, Amy; Dickens, Hunter J; Holroyd, Michael J; Driscoll, Colin L W; Link, Michael J; Morris, Jonathan (Journal of Neurological Surgery Part B: Skull Base, 2021)
Background 3D printing—also known as additive manufacturing—has a wide range of applications. Reproduction of low-cost, high-fidelity, disease- or patient-specific models presents a key developmental area in simulation and education research for complex cranial surgery.Methods Using cadaveric dissections as source materials, skull base models were created, printed, and tested for educational value in teaching complex cranial approaches. In this pilot study, assessments were made on the value of 3D printed models demonstrating the retrosigmoid and posterior petrosectomy approaches. Models were assessed and tested in a small cohort of neurosurgery resident subjects (n = 3) using a series of 10 radiographic and 2 printed case examples, with efficacy determined via agreement survey and approach selection accuracy.Results All subjects indicated agreement or strong agreement for all study endpoints that 3D printed models provided significant improvements in understanding of neuroanatomic relationships and principles of approach selection, as compared to 2D dissections or patient cross-sectional imaging alone. Models were not superior to in-person hands-on teaching. Mean approach selection accuracy was 90% (±13%) for 10 imaging-based cases, or 92% (±7%) overall. Trainees strongly agreed that approach decision-making was enhanced by adjunctive use of 3D models for both radiographic and printed cases.Conclusion 3D printed models incorporating skull base approaches and/or pathologies provide a compelling addition to the complex cranial education armamentarium. Based on our preliminary analysis, 3D printed models offer substantial potential for pedagogical value as dissection guides, adjuncts to preoperative study and case preparation, or tools for approach selection training and evaluation.
Keywords: neuroanatomy; 3D printing; skull base; cerebrovascular; complex cranial surgery; pedagogy; simulation